The Effect of Financial Distress, Good Corporate Governance, and Institutional Ownership on Tax Avoidance (Empirical Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange for the 2016-2019 Period) - Fauzan, F; Arsanti, Pingkhan Mutia Dewi; Fatchan, Ilham Nuryana (Universitas Muhammadiyah Surakarta, 2021)
This study aims to provide empirical evidence about the effect of financial distress, good corporate governance and institutional ownership on tax avoidance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2019 period. This research was designed using quantitative research. The data used in this study were obtained from the website www.idx. co.id and the company’s financial statements. The sampling technique used purposive sampling and obtained a sample of 60 data samples during the 4-year observation period. After the data experienced outliers as much as 10 data so that the total sample studied decreased to 50 data. The collected sample data were analyzed using the SPSS version 25 program using the classical assumption test, then hypothesis testing was carried out using the multiple linear regression analysis method, and statistical test analysis. The results of these tests indicated that research with managerial ownership variables, board of director size and institutional ownership had a significant effect on tax avoidance. Meanwhile, the financial distress variable, the size of the independent board of commissioners and the audit committee had no significant effect on tax avoidance.